Gut evacuation rate as a tool for revealing feeding patterns in the invasive round goby (Neogobius melanostomus) under different feeding modes, food types and temperatures - Natalia Z. Szydłowska; Marek Let; Pavel Franta; Miloš Buřič; Susanne Worischka; Luise Richter; Bořek Drozd (Aquatic Invasions, 2024)
The round goby (Neogobius melanostomus) is a well-known invasive fish. Knowledge of its feeding habits and means of food processing is key in understanding its impact on aquatic food webs. The present study assessed the gut evacuation rate of round gobies feeding on three different types of prey occurring naturally in the diet of this species (small native freshwater clams, an invasive amphipod and chironomid larvae), at two different temperatures (14 and 20 °C) and under different food availability scenarios (continuous and non-continuous feeding). Gut evacuation rates varied significantly between the prey availability scenarios and, specifically, round gobies processed prey significantly faster in the continuous feeding mode when food was regularly available than when fed only once. The highest evacuation rates were detected for individuals fed with clams, in which complete gut clearance was observed within 16 h, compared to within 24 h and 36 h for chironomid larvae and amphipods, respectively. Our study shows that round gobies evacuate chironomid and mollusc prey most rapidly, which suggests that potentially the highest predatory pressure will be exerted on these prey types, assuming that all three prey species are locally present. The slower processing and digestion of amphipods may be due to their bulkier shape, which makes them more difficult to swallow. The relatively high evacuation efficiency of the round goby observed in the continuous feeding mode suggests overall increased pressure on food resources, thereby potentially reducing availability for other consumers and accelerating resource depletion, mainly driven by the high local densities of the round goby populations.